Assessing students’ learning outcomes under informatization of professional education - Olga I. Vaganova, Zhanna V. Smirnova; Elena N. Galkina, Viktor A. Sokolov (Opción, 2019)
The paper covers aspects of assessing learning outcomes of students using information and communication technologies (ICT). Within a competency-based approach, ICT provides such interactive educational and evaluation tools as forums, cases, web-quests, etc. It was identified that application of ICT in the professional education facilitates presentation of the study results, the degree of mastering competences, and readiness for labour activities. In conclusion, ICT enables students to build up an individual and comfortable learning path and teachers – to update the content of education, give lessons of any type and more effectively monitor the results of students’ learning activity